Knowledge Management Strategy for Enhancing Public Information Services at Diskominfo Medan - Muhammad Alfahmi; Muhammad Alfikri (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the strategy of implementing knowledge management in optimizing programs and activities of the Medan City Communication and Information Service (Dinas Komunikasi dan Informatika/Diskominfo), especially in the dissemination of public information. The background of this study is based on the importance of effective knowledge management so that public information can be delivered quickly, precisely, and accurately to the public. The research method used is qualitative with a case study approach. Data were collected through interviews, observations, and documentation studies. The results of the study indicate that the implementation of knowledge management in the Medan City Diskominfo includes three main stages: knowledge acquisition, knowledge storage and management, and knowledge distribution. Although there have been initiatives in the implementation of information systems and internal training, challenges are still found such as limited human resources, lack of a culture of knowledge sharing, and suboptimal use of information technology. This study recommends increasing human resource capacity, developing an integrated digital platform, and strengthening internal policies to support a culture of knowledge sharing in order to improve the quality of public information services.